Policy Proposals to Promote Active Learning in History Education in Schools under The Surin Primary Educational Service Area Office 1: Policy Proposals to Promote Active Learning in History Education in Schools under The Surin Primary Educational Service Area Office 1 - Suwanla, Suradit; Yodsala, Suphatanakris; Kakkeaw, Vasanchai; Polsri, Urid (RATANABUTH JOURNAL, 2025)
This policy research aimed to 1) study the level of school administration to promote active learning in history education, and 2) develop policy proposals to promote active learning in history education in schools under the Surin Primary Educational Service Area Office 1. The research design employed a mixed-methods approach and was conducted in two phases. In Phase 1, the study level of school administration, the sample consisted of 330 participants, including school administrators and heads of social studies, religion, and culture department within the Surin Primary Educational Service Area Office 1, selected through stratified random sampling. In Phase 2, the development of policy proposals, derived from in-depth interviews with nine key informants, followed by an evaluation of the propriety and feasibility of the proposed policies by nine experts. The research instruments included questionnaires, semi-structured interview forms, and policy proposal propriety and feasibility evaluation forms. The statistical methods used for data analysis included frequency, percentage, mean, standard deviation, and content analysis. The results of this research were as follows: 1. The level of school administration to promote active learning in history education in schools under the Surin Primary Educational Service Area Office 1, both overall and across specific dimensions, was rated highly. 2.The policy proposals to promote active learning in history education in schools under the Surin Primary Educational Service Area Office 1 comprised of five key dimensions: 1) Educational Administration, 2) Curriculum and Instructional Processes, 3) Personnel Development, 4) Learning Materials and Learning Ecosystems, and 5) Collaboration with Local Networks. The propriety and feasibility evaluation of the policy proposals was highly rated, confirming that the policies are applicable and can be implemented.